The role of time-driven activity based costing in reducing the company costs and increasing the earnings: Case study of Athmani diary in Khenchla - Aziz, Loudjani; Amel, Guentri (The International tax journal, 2025)
This study sheds light on the time-driven activity based costing TD-ABC and on its effect on the increase of the company’s profits. In so doing, the study focuses on all the technical specifications of the study product, which is the milk case made by Athmani diary in Khenchla, and tries to coordinate the different determinants of the operational costs that increase the added value. In addition, it excludes the activities that neither add value nor improve the activity. Findings show that the application of TD-ABC allows reducing the costs of the milk liter in the study diary with a rate of 16.41%. Besides, the system is based on essential and strategic points, namely the control, decrease, or omission of the operational costs to stop wasting the available financial resources and regulate the earnings. Moreover, the system identifies the cost items that add a service to the company and deletes or excludes the items that do not add a value in order to improve the earnings, decrease the costs, and foste the competitive advantage.